Recent applications of computational methods to allosteric drug discovery - Govindaraj, Rajiv Gandhi; Thangapandian, Sundar; Schauperl, Michael; Denny, Rajiah Aldrin; Diller, David J. (Frontiers in Molecular Biosciences, 2023)
Interest in exploiting allosteric sites for the development of new therapeutics has grown considerably over the last two decades. The chief driving force behind the interest in allostery for drug discovery stems from the fact that in comparison to orthosteric sites, allosteric sites are less conserved across a protein family, thereby offering greater opportunity for selectivity and ultimately tolerability. While there is significant overlap between structure-based drug design for orthosteric and allosteric sites, allosteric sites offer additional challenges mostly involving the need to better understand protein flexibility and its relationship to protein function. Here we examine the extent to which structure-based drug design is impacting allosteric drug design by highlighting several targets across a variety of target classes.